Genetic Gain for Soybean Seed Protein, Oil, and Yield in a Recombinant Inbred Line Population. (13th November 2018) - Wiggins, Benjamin; Wiggins, Suzannah; Cunicelli, Mia; Smallwood, Chris; Allen, Fred; West, Dennis; Pantalone, Vince
Abstract: The use of soybean [ Glycine max (L.) Merrill] is widespread, with applications in food, fuel, livestock feed, and industrial products. We developed a soybean population of 239 F4 ‐derived recombinant inbred lines (RIL) from the cross "5601T" × U99‐310255 to estimate the heritability and genetic gain for seed protein, oil, and yield, and to assess the utility of making selections for these important traits. Heritability estimates on an entry means basis for protein (0.78), oil (0.65), seed yield (0.38) varied by trait with regard to genetic influence. Genetic gain was calculated for each trait at 5%, 10%, 15%, and 20% selection intensities. With the genetic gain that was obtained through the selections for each trait, some lines excelled above that of the checks and parents in this population. The second and third highest yielding selections (56U99‐081 and 56U99‐244) are notable in producing 50.2% and 49.8% meal protein, respectively, while maintain high yields above the high‐yielding parent, 5601T. Seeking balance for these important soybean traits is essential for breeders looking to make optimal improvements for the wide variety of soybean uses. Further research on this population could prove to be of value to breeding programs wishing to increase seed yield, oil, and protein.